Analysis of the System and procedures Procurement of Goods and Services at PT X TBK in the Perspective of Effectiveness, Efficiency, and Transparency - Aisha Inggitha Putri Haryoso; Murti Widyaningsih (Journal of Social Research, 2026)
This research aims to analyze the system and procedures for the procurement of goods and services implemented at PT X Tbk using a quantitative approach. The background of this research is the strategic role of procurement in corporate governance and the existence of several indications of problems in the procurement process at the company. The research method used is quantitative descriptive, with data obtained from internal company documents, structured procurement records, and questionnaires distributed to 17 respondents involved in the procurement process. Data analysis was carried out to assess the levels of effectiveness, efficiency, and transparency in the procurement process, encompassing validity and reliability tests, classical assumption tests, and hypothesis testing using multiple linear regression. The findings indicate that the procurement procedure at PT X Tbk is carried out through systematic stages, from the submission of procurement requests to the contract finalisation stage. The transparency variable was rated very highly by respondents and was the only variable that satisfied the reliability test. However, the effectiveness and efficiency variables showed reliability values below the acceptable threshold, indicating inconsistencies in respondents' perceptions. The regression analysis revealed that efficiency has a positive and significant effect on the procurement system and procedures, while effectiveness and transparency do not show a significant effect. The implication of this research is the need for PT X Tbk to focus on improving efficiency in the procurement process and to re-evaluate the measurement instruments for effectiveness and transparency to ensure more consistent and reliable results in the future.